A new species of Phenacorhamdia Dahl 1961 (Siluriformes: Heptapteridae) from the Paranapanema River basin, southeastern Brazil - Silva, Gabriel S. C. (Zootaxa, 2020)
A new species of Phenacorhamdia is described from Paranapanema River, Upper Paraná River basin, southeastern Brazil. The new species is distinguished from congeners by the combination of following characters 45−46 vertebrae; an entirely dark-brown body; nine pleural ribs; eight branched rays in upper lobe of caudal fin; seven branched rays in pectoral fin; 13 anal-fin rays with 9−10 branched; first basal radial inserted at the 13th vertebrae and eight branchiostegal rays.